Rapid evaluation of rabies control program: 30-cluster survey in rural area of Perambalur district, Tamilnadu, India - Kumar, Rakesh; Sinha, Sati P. (International Journal Of Community Medicine And Public Health, 2016)
Background: Rabies is a fatal and neglected zoonotic disease transmitted mostly by dog bites. Recently, Tamil Nadu, India has made a coordinated effort involving public health and animal husbandry agencies and put in place interventions like ABC – AR and universal vaccine supply to address this problem. With this background the following study was done to study the effect of rabies control efforts by Tamil Nadu government on incidence of dog bite and on the knowledge, attitude & practice of dog care & management of dog bite. Methods: A 30-cluster survey was done to study 300 subjects. Information was collected using structured questionnaire regarding history of dog bite in past one year and its management practices, knowledge on pet dog care, activities done by government for control of dog population, disease transmitted by dog bite and regarding management of dog bite. The data was entered and analyzed in epi_info 6.04. Results: Study found a high incidence of dog bite in general population with incidence being 31.1 per 1000 population/year. Children less than 15 years (RR =1.86) and low SES (RR=2.54) are more vulnerable to dog bite injuries. Conclusions: From present study it was found an unsatisfactory pet care practices & very low awareness regarding rabies, dog population control program and management of dog bite injuries. Management of dog bites injuries was grossly inadequate.